(untitled) (American Journal of Islam and Society, 1992)
The Lexical and Technical Meanings of Taqlid The lexical meaning and structure of the word “taqlid” clearly indicate the negative connotations surrounding its technical meaning as well as its retention of much of the literal sense. The Arabic root q-ld comes from qald, which means ”to twist or to twine.” As most necklaces were twined or braided, the word came to refer to necklaces, and the active form of the verb (taqlid) to putting on a necklace. An example from early Arabic poetry uses taqlid in this sense: They placed on her (round her neck) amulets, To ward off evildoers and enviers. The same word is also used to refer to the marking made around the neck of an animal destined for sacrifice during hajj. In addition, a camel is said to be “necklaced” (muqallad) when a rope is placed over its head and around its neck. In a less literal usage, this word has the sense of placing responsibility on an individual, as in “The sultan charged (q-I-d) someone with a duty,” as charging a person in such a manner resembles putting a necklace around hidher neck. Here, the one who accepts the responsibility is as one who wears a necklace.‘ The classical uh’di efine taqlid as one’s ”acceptanceo f another‘s madhhQb without knowing the other person’s justification.” (In this definition, Madhhab includes everydung that fills within the purview of ijtihad.) Although the fuqaha’ have defined the term in different ways, all agree that it signifies the acceptance of and acting upon another‘s word without trying to substantiate it. In other words, ...